From The Club Stage to the National Scene: How Mass Media Interpreted Two Comedians as Important Immigrant Voices - Dahl, John Magnus (Javnost-The Public, 2019)
This article investigates how comedians with an immigrant background gain political relevance, taking two contemporary comedians from Norway and Sweden as cases. The study uses media's interpretive power as a way to explore Habermas’ ([1996]. Between Facts and Norms: Contributions to a Discourse Theory of Law and Democracy. Cambridge, MA: MIT Press) claim that the borders between the cultural and the political public spheres are porous. A reading of the press coverage of the comedians is used to discover patterns in how media interpreted the comedians as immigrant voices and as humourists. It is demonstrated how the comedians get moulded into certain positions through mass media interpretations, as well as explained where these interpretations come from historically. Furthermore, it is shown that the coverage of the two comedians to a large degree conformed to existing immigration discourse, challenging the view of comedy as a subversive force.